Challenges of working mothers among female civil servants in Jakarta and Bogor: An existentialism feminist analysis of Simone de Beauvoir - Putri, Fadilla Dwianti; Siscawati, Mia (Program Pascasarjana Universitas Negeri Yogyakarta, 2023)
This research explores the experiences of female civil servants in Jakarta and Bogor regarding the social constructions that shape their roles as wives and mothers. This research uses a qualitative approach with a case study method. Data were collected through in-depth interviews and observations during October-November 2022 using Simone de Beauvoir's feminist existentialism framework. This study found that female civil servants are still expected to bear the full burden of domestic work despite their role in the public sphere. As a result, women often experience a double burden and are hindered from getting promoted. This is due to the view that women's role in the public sphere is secondary, in line with the legacy of the